The Disruption of Digital Evidence in Criminalizing the Spread of Deepfakes: A Positive Criminal Law Analysis and the Perspective of Al-Fiqh Al-Jinayah - Vania Andari Damanik (al-Afkar, Journal For Islamic Studies, 2026)
The rapid development of artificial intelligence (AI), particularly deepfake technology, has significantly disrupted the criminal law evidentiary system, especially concerning the reliability of electronic evidence. Deepfake enables highly realistic manipulation of audio-visual content, making it increasingly difficult to distinguish between authentic and fabricated evidence. This poses serious challenges to both the evidentiary process and criminal liability in technology-based crimes. This study aims to analyze the disruption of digital evidence caused by deepfake technology and to examine the challenges of criminal liability based on Law Number 1 of 2024 concerning the Second Amendment to the Electronic Information and Transactions Law (ITE Law) and the perspective of Islamic criminal law (fiqh jinayah).This research employs a normative legal method with a statutory and comparative approach. The data consist of primary and secondary legal materials, analyzed qualitatively using a descriptive-analytical method. The results indicate that although Indonesian positive law recognizes electronic evidence as legally valid, the regulation regarding its validity and verification mechanisms particularly for evidence generated through deepfake technology remains inadequate. This creates legal uncertainty and potentially disrupts the pursuit of material truth in criminal proceedings. Furthermore, issues of criminal liability become more complex due to difficulties in identifying perpetrators and proving elements of intent or negligence. From the perspective of Islamic criminal law, evidentiary principles emphasize authenticity and credibility, allowing electronic evidence to be accepted through qiyas, provided that strict standards of validity are fulfilled.